HEALTH LITERACY AND HYGIENE PRACTICES: IMPACT ON SCABIES PREVENTION IN ISLAMIC ELEMENTARY SCHOOL STUDENTS - Reksa, Moh. Bahrawi Angga; Kusyani, Asri; Vidhiastutik, Yusiana; Putra, Kusuma Wijaya Ridi (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2025)
Background: Scabies is a highly contagious skin disease frequently found in communal environments, including Islamic elementary schools. Limited health literacy and poor hygiene practices among students contribute to its continued spread. Objectives: This study aimed to examine the relationship between health literacy, hygiene practices, and scabies prevention behaviors among Islamic elementary school students. Methods: A cross-sectional analytic study was conducted involving 50 students at Madrasah Ibtidaiyah (MI) Miftahul Ulum Blaban, Pamekasan, East Java. Data were collected using structured questionnaires assessing health literacy, hygiene practices, and scabies prevention behaviors. Spearman’s rank-order correlation was used to analyze the relationship between variables, with a significance level of p < 0.05. Results: The majority of students (60%) demonstrated poor hygiene behavior, and 40% had low health literacy. A significant positive correlation was found between health literacy and scabies prevention (r = 0.479, p < 0.001), as well as between hygiene practices and scabies prevention (r = 0.455, p < 0.001). Conclusion: Higher levels of health literacy and improved hygiene practices are associated with better scabies prevention behaviors among Islamic elementary school students. Strengthening school-based health education is essential to reduce the incidence of scabies in similar educational environments.